Preliminary characterization of Plasmodium vivax sporozoite antigens as pre-erythrocytic vaccine candidates - Nicholas J. (2023)
Plasmodium vivax pre-erythrocytic (PE) vaccine research has lagged far behind efforts to develop Plasmodium falciparum vaccines. There is a critical gap in our knowledge of PE antigen targets that can induce functionally inhibitory neutralizing antibody responses. To overcome this gap and guide the selection of potential PE vaccine candidates, we considered key characteristics such as surface exposure, essentiality to infectivity and liver stage development, expression as recombinant proteins, and functional immunogenicity. Selected P. vivax sporozoite antigens were surface sporozoite protein 3 (SSP3), sporozoite microneme protein essential for cell traversal (SPECT1), sporozoite surface protein essential for liver-stage development (SPELD), and M2 domain of MAEBL. Sequence analysis revealed little variation occurred in putative B-cell and T-cell epitopes of the PE candidates. Each antigen was tested for expression as refolded recombinant proteins using an established bacterial expression platform and only SPELD failed. The successfully expressed antigens were immunogenic in vaccinated laboratory mice and were positively reactive with serum antibodies of P. vivax-exposed residents living in an endemic region in Thailand. Vaccine immune antisera were tested for reactivity to native sporozoite proteins and for their potential vaccine efficacy using an in vitro inhibition of liver stage development assay in primary human hepatocytes quantified on day 6 post-infection by high content imaging analysis. The anti-PE sera produced significant inhibition of P. vivax sporozoite invasion and liver stage development. This report provides an initial characterization of potential new PE candidates for a future P. vivax vaccine.